Modeling the association between HR variability and illness in elite swimmers. - Hellard, P.; Guimaraes, F.; Avalos, M.; Houel, N.; Hausswirth, C.; Toussaint, J. F. (Medicine & Science in Sports & Exercise, 2011)
Purpose: To determine whether HR variability (HRV), an indirect measure of autonomic control, is associated with upper respiratory tract and pulmonary infections, muscular affections, and all-type pathologies in elite swimmers.